Characteristics and Therapy of Patients with Bartholin's Cysts in An Indonesian Tertiary Hospital - Djusad, Suskhan; Putra, Dafnil Akhir (Majalah Kedokteran Bandung, 2024)
A blocked duct of the Bartholin gland causes mucus accumulation and a fluid-filled sac, i.e., a Bartholin cyst, that can develop into an abscess when infected. This study specifically explored the characteristics and treatment Bartholin cysts or abscesses in patients registered at the obstetrics and gynecology clinic of Dr. Cipto Mangunkusumo National General Hospital, a tertiary hospital in Indonesia. This retrospective and descriptive study utilized data from patients registered at the hospital from July 2021 to July 2023. Bartholin cysts were found to be more common in patients aged 40 to 45 (57.1%) with a non-working status (71.4%), and  married (90.5%). Cysts were found to be 1 to 3 cm in size (52.4%) and occured unilaterally (95.2%). Four of the fourteen patients complained of recurring Bartholin cysts. On history and clinical examinations, 20 (95.2%) patients reported the presence of lumps. Antibiotics were the most commonly used treatment, with 15 of 21 Bartholin cyst patients (71.4%) receiving them. Obtaining data on the demographic of patient characteristics is essential when providing appropriate health care. Clinical considerations such as cyst size, patient age, symptoms, and history of recurrent Bartholin cysts or abscesses influence the choice of comprehensive medical and surgical management.